Epidemiology of injuries in National Collegiate Athletic Association men's swimming and diving: 2014-2015 through 2018-2019 - Boltz, A. J.; Robison, H. J.; Morris, S. N.; D'Alonzo, B. A.; Collins, C. L.; Chandran, A. (Journal of Athletic Training, 2021)
Context: The National Collegiate Athletic Association (NCAA) has sponsored men's swimming and diving since 1937. Background: Routine examinations of men's swimming and diving injuries are important for identifying emerging injury-related patterns. Methods: Exposure and injury data collected in the NCAA Injury Surveillance Program during the 2014-2015 through 2018-2019 academic years were analyzed. Injury counts, rates, and proportions were used to describe injury characteristics, and injury rate ratios were used to examine differences in injury rates. Results: The overall injury rate was 1.56 per 1000 athlete-exposures (AEs) for swimmers and 1.52 per 1000 AEs for divers. Shoulder (27.0%) injuries accounted for the largest proportion of all swimming injuries, and most injuries were attributed to overuse mechanisms (42.6%). Shoulder (23.3%) and trunk (23.3%) injuries accounted for the largest proportion of all diving injuries, and most injuries resulted from surface contact (32.6%). Conclusions: Findings were consistent with existing literature on swimming and diving. The need for continued surveillance, coupled with more robust participation by swimming and diving programs was also highlighted.